A study of residual elastic strain distribution in an AZ91 Mg alloy bar loaded in four point bending - Prakash, D; Vorster, W; Zhang, S; Korsunsky, A (Trans Tech Publications, 2008)
This paper presents a study of the residual strain field within a high pressure die cast (HPDC) AZ91 Mg alloy bar subjected to four point bending. The technique employed for this purpose is high energy synchrotron X-ray diffraction. Strain scanning using polychromatic X-ray beam allows the collection of multiple peak diffraction patterns and monitoring of small peak shifts as a function of beam position. These shifts allow collective interpretation in terms of the equivalent macroscopic residual elastic strain. Residual elastic strain distributions were studied in the sections subjected to pure bending and also in sections of contact between the sample and the rollers. These experimental results are compared with the predictions from a finite element analysis of contact and deformation. Good agreement is found between the modelled and measured results. It is hoped that these results help improved understanding of complex deformation behaviour of thin-walled HPDC AZ91 components and provide useful background information for lifting assessment of such structures.